The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41398-022-02190-8
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression: a developed and validated model predicting individual risk in new mothers

Abstract: Postpartum depression (PPD) is a serious condition associated with potentially tragic outcomes, and in an ideal world PPDs should be prevented. Risk prediction models have been developed in psychiatry estimating an individual’s probability of developing a specific condition, and recently a few models have also emerged within the field of PPD research, although none are implemented in clinical care. For the present study we aimed to develop and validate a prediction model to assess individualized risk of PPD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Postpartum depression, panic attacks, and PTSD due to their traumatic pregnancies were reported by some mothers in their blogs, which confirmed results from multiple previous research studies. 18,22,24 Using Danish population registers, Munk-Olsen et al 21 reported that HG was one of the 4 most significant predictors of postpartum depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum depression, panic attacks, and PTSD due to their traumatic pregnancies were reported by some mothers in their blogs, which confirmed results from multiple previous research studies. 18,22,24 Using Danish population registers, Munk-Olsen et al 21 reported that HG was one of the 4 most significant predictors of postpartum depression.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatally, 29% of the mothers with HG had probable depression compared to 7% of the control subjects (P = .002). Munk-Olsen et al 21 developed a prediction model for postpartum depression using data from the Danish population registers for 6402 postpartum depression cases and 2379 validation samples. HG was 1 of the 4 most significant predictors of postpartum depression.…”
Section: Maternal Psychological Morbiditymentioning
confidence: 99%
“…For each comparison, we shall also look at the node split model, thus helping us to quantify comparison-specific inconsistency to estimate deficiencies in transitivity. We have identified potential effect modifiers (Table 3) from the literature [15][16][17][18] and will assess the distribution of effect modifiers to judge if the transitivity assumption holds. For those that prove to be a study-level parameter, then we plan to explore the impact of this on our network estimates by employing network meta-regression.…”
Section: Exploration Of Model Fitness Transitivity and Inconsistencymentioning
confidence: 99%
“…Previous depression diagnosis [15][16][17] b. Lower education status [15] c. Unemployment [15] d. Low socioeconomic status [16] e. Low levels of social support [16] f. Advanced maternal age [17] g.…”
Section: Exploration Of Model Fitness Transitivity and Inconsistencymentioning
confidence: 99%
“…The existing early intervention paradigm is based on a USPSTF Grade B recommendation wherein counseling is provided to women with 1 or more established risk factors for PPD, such as a history of depression or recent intimate partner violence. 6 The current approach for identifying at-risk patients is crude at best and represents an opportunity to mobilize available technologies such as machine learning (ML) in a way that can improve health outcomes. The lack of effective screening tools is a public health issue because early interventions in at-risk people can minimize the morbidity and mortality of PPD.…”
Section: Introductionmentioning
confidence: 99%